Empire Burlesque The Fate of Critical Culture in Global America - O'Hara, Daniel T. (Duke University Press, 2003)
Empire Burlesque traces the emergence of the contemporary global context within which American critical identity is formed. Daniel T. O'Hara argues that globalization has had a markedly negative impact on American cultural criticism, circumscribing both its material and imaginative potential, reducing much of it to absurdity. By highlighting the spectacle of its own self-parody, O'Hara aims to shock U.S. cultural criticism back into a sense of ethical responsibility.Empire Burlesque presents several interrelated analyses through readings of a range of writers and cultural figures including Henry James, Freud, Said, De Man, Derrida, and Cordwainer Smith (an academic, spy, and classic 1950s and 1960s science fiction writer). It describes the debilitating effects of globalization on the university in general and the field of literary studies in particular, it critiques literary studies' embrace of globalization theory in the name of a blind and vacant modernization, and it meditates on the ways critical reading and writing can facilitate an imaginative alternative to institutionalized practices of modernization. Drawing on Lacanian psychoanalytical theory, it diagnoses contemporary American Studies as typically driven by the mindless abjection and transference of professional identities.A provocative commentary on contemporary cultural criticism, Empire Burlesque will inform debates on the American university across the humanities, particularly among those in literary criticism, cultural studies, and American studies
Description based on online resource; title from PDF title page (publisher's Web site, viewed 12. Dez 2020)
Keywords: SOCIAL SCIENCE / Sociology / General; American literature -- History and criticism -- Theory, etc; Criticism -- United States -- History -- 20th century; Journalism -- United States; Literature -- History and criticism -- Theory, etc; Mass media and culture -- United States